Protective Immunity Against Neospora caninum Infection Induced by 14-3-3 Protein in Mice - Li, Shan; Zhang, Nan; Liu, Shaoxiong; Li, Jianhua; Liu, Li; Wang, Xiaocen; Li, Xin; Gong, Pengtao; Zhang, Xichen (Frontiers in Veterinary Science, 2021)
Neospora caninum is an apicomplexan parasite that infects many mammals and remains a threatening disease worldwide because of the lack of effective drugs and vaccines. Our previous studies demonstrated that N. caninum 14-3-3 protein (Nc14-3-3), which is included in N. caninum extracellular vesicles (NEVs), can induce effective immune responses and stimulate cytokine expression in mouse peritoneal macrophages. However, whether Nc14-3-3 has a protective effect and its mechanisms are poorly understood. Here, we evaluated the immune responses and protective effects of Nc14-3-3 against exposure to 2 × 107 Nc-1 tachyzoites. Antibody (IgG, IgGl, and IgG2a) levels and Th1-type (IFN-γ and IL-12) and Th2-type (IL-4 and IL-10) cytokines in mouse serum, survival rates, survival times, and parasite burdens were detected. In the present study, the immunostimulatory effect of Nc14-3-3 was confirmed, as it triggered Th1-type cytokine (IFN-γ and IL-12) production in mouse serum 2 weeks after the final immunization. Moreover, the immunization of C57BL/6 mice with Nc14-3-3 induced high IgG antibody levels and significant increases in CD8+ T lymphocytes in the spleens of mice, indicating that the cellular immune response was significantly stimulated. Mouse survival rates and times were significantly prolonged after immunization; the survival rates were 40% for Nc14-3-3 immunization and 60% for NEV immunization, while mice that received GST, PBS, or blank control all died at 13, 9, or 8 days, respectively, after intraperitoneal N. caninum challenge. In addition, qPCR analysis indicated that there was a reduced parasite burden and diminished pathological changes in the mice immunized with Nc14-3-3. Our data demonstrate that vaccination of mice with Nc14-3-3 elicits both cellular and humoral immune responses and provides partial protection against acute neosporosis. Thus, Nc14-3-3 could be an effective antigen candidate for vaccine development for neosporosis.